Improving Flood Damage Assessment Models in Italy - Mattia Amadio; Jaroslav Mysiak; Lorenzo Carrera; Elco Koks (Fondazione Eni Enrico Mattei (FEEM), 2015)
Flood damage assessments are often based on Stage-Damage Curve (SDC) models that estimate economic damage as a function of flood characteristics, typically flood depths, and land use. SDCs are developed through site-specific analysis but rarely adjusted to economic circumstances in areas to which they are applied. In Italy, assessments confide in SDC models developed elsewhere, even if empirical damage reports are collected after every major flood event. In this paper we tested, adapted and extended an up-to-date SDC model using flood records from Northern Italy. The model calibration is underpinned with empirical data from compensation records. Our analysis takes into account both physical asset and foregone production losses, the latter measured amidst the spatially distributed gross added value (GVA).
Keywords: Q54; 330; Flood Risk Management; Stage Depth Damage Curves; Economic Damage; Disaster Losses; Italy